Validity of ultrasound-guided aspiration needle biopsy in the diagnosis of micrometastases in sentinel lymph nodes in patients with cutaneous melanoma - Šijan, Goran; Kozarski, Jefta V; Stepić, Nenad; Milojević, Saša; Stefanović, Dara; Tatomirović, Željka; Jauković, Ljiljana; Vesanović, Svetlana; Rajović, Milica (Vojnosanitetski pregled, 2017)
Background/Aim. Cutaneous melanoma is one of the most aggressive solid cancers, that develops local, regional and distant metastases. The presence of metastases in lymph nodes is in correlation with Breslow tumor thickness. According to various researches, in melanoma with more than 4 mm Breslow thickness, lymph node micrometastases can be found in 60–70% of cases. Sentinel lymph nodes biopsy is a diagnostic procedure for lymph node micrometastasis detection, which is necessary for disease staging. In recent studies, ultrasound-guided fine needle aspiration with cytology (US FNAC) of the sentinel lymph node was used as less invasive procedure, but is not accepted as the standard procedure. The goal of this work was to define sensitivity, specification and precision of the ultrasound-guided fine needle aspiration method in comparison with standard sentinel lymph node biopsy. Methods. After obtaining the Ethics Committee’s permission, from 2012 to 2014 a total of 60 patients with cutaneous melanoma were enrolled, and divided into three groups: group I with thin melanoma, group II with intermediate thickness melanoma and group III with thick melanoma. The presence of micrometastases in sentinel regional lymph nodes was analyzed by US FNAC. The results obtained were compared to sentinel lymph nodes biopsy (SLNB) results. The golden standard for calculating the specific, sensitive and precise characteristics of the method of US FNAC of sentinel lymph nodes was histopathologic lymph node examination of sentinel lymph nodes acquired through biopsy. Results. Detection rate of US FNAC was 0% in the group I, 5% in the group II and 30% in the group III. SLNB detection rates were: 10% in the group I, 15% in the group II, and 45% in the group III. In melanoma thicker than 4 mm, 15% of the patients were false negative by US FNAC. The sensitivity of US FNAC for all the patients was 50%: in the group I, 0%; in the group II, 33.3%; and in the group III, 66.6%. The method specificity for all examined patients was 100% and accuracy 88%: group I, 90%; group II, 90%; group III, 85%. The FNAC and SLNB micrometastasis detection rate was significantly higher in melanoma with Breslow thickness > 4 mm (group 3) in comparison to thin and intermediate thickness tumors. Conclusion. The method of ultrasound-guided fine needle aspiration of sentinel lymph nodes, according to its sensitivity, has a place in the diagnostics of micrometastasis in regional lymph nodes only in thick melanoma, but not in thin and intermediary thickness melanoma. The results must be confirmed in a larger number of patients. If this observation could be confirmed, it would rationalize treatment of patients with thick melanoma, decrease the number of operations and shorten the time to make the diagnosis.
Keywords: endoscopic ultrasound-guided fine needle aspiration; neoplasm; micrometastasis; sentinel lymph node biopsy; skin; melanoma; diagnosis; sensitivity and specificity